Act Naturally: The Beatles on Film - Matteo, Steve (Rowman & Littlefield Publishers, 2023)
The Beatles produced five films during their time together: A Hard Day’s Night, Help!, Magical Mystery Tour, Yellow Submarine, and Let It Be. Some were cinematic successes, and some were not, but—along with subsequent reissues, bonus material, and Peter Jackson’s The Beatles: Get Back, a documentary companion to Let It Be—they comprise an endlessly fascinating document of key phases in the group’s career. In this comprehensive deep-dive into the band’s movies, author and longtime music journalist Steve Matteo follows the origins, filming, and often frenzied fan reception of projects from the 1964 premiere of A Hard Day’s Night through 1970’s Let It Be to the release of Get Back in 2022. Matteo explores the production process, original theatrical film releases, subsequent VHS, DVD, and Blu-ray releases, and bonus materials, along with the US and UK soundtracks. In addition to copious anecdotes and behind-the-scenes details, he also places these films in their larger context, a period of unprecedented artistic and commercial innovation in British and world cinema. Filled with stories and insights that will satisfy collectors, buffs, and casual fans alike, this is the definitive account of an underappreciated part of the Beatles’ creative output.